(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Cutibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus are commonly associated with the pathogenesis of acne vulgaris. Skincare products that contain natural ingredients have become a trend to treat acne. Dr.Ridz Anti-Acne Nanoserum® product was formulated with the extract of Cassia alata leaf and Piper betle. The aim of this study was to determine the antibacterial activity of this formulated product against against C. acnes, S. epidermidis, and S. aureus. The minimum inhibitory concentration (MIC) value and the minimum bactericidal concentration (MBC) were determined using a broth microdilution and a streak plate method, respectively. The rate of killing by this product was tested using time-kill assay (TKA) at 0.5x MIC, 1x MIC, and 2x MIC with incubation periods of 2, 4, 6, 8 10, 12, and 24 hours. The MIC values showed that this product inhibited S. epidermidis and S. aureus better than C. acnes. From the calculation of the MBC/MIC ratio, this product showed bactericidal effects against all tested bacteria. The time-kill studies showed that the killing effect of this product was concentration-dependent, and the highest antibacterial activity was observed at the concentration of 2x MIC against all tested bacteria. In conclusion, Dr.Ridz Anti-Acne Nanoserum® exhibits the best antibacterial activities against S. epidermidis and showed a bactericidal effect towards all tested bacteria. .